Scavenger receptor B1 post-translational modifications in Rett syndrome - Sticozzi, Claudia; Belmonte, Giuseppe; Pecorelli, Alessandra; Cervellati, Franco; Leoncini, Silvia; Signorini, Cinzia; Ciccoli, Lucia; De Felice, Claudio; Hayek, Joussef; Valacchi, Giuseppe (FEBS letters, 2013)
•Rett patients have an alterated plasma lipid profile.•SRB1 (HDL receptor) is low in Rett fibroblasts.•Rett fibroblasts have high level of HNE with formation of HNE–SRB1 adducts.•SRB1 is ubiquitinated. The modulation of the HDL receptor scavenger receptor B1 (SRB1) was evaluated in skin fibroblasts isolated from patients with Rett syndrome (RTT), a genetic form of infantile autism. Patients showed an altered plasma lipid profile, while their skin fibroblasts showed a dramatic reduction in SRB1 (immunogold, Western blot and immunohistochemistry). The decreased SRB1 levels were demonstrated to be the consequence of its binding with 4-hydroxy-2-nonenal (4HNE), a product of lipid peroxidation, and its increased ubiquitination. Our findings show for the first time a loss of SRB1 in RTT cells and its relationship with a chronic oxidative stress status.